2014
DOI: 10.4172/2168-9652.1000150
|View full text |Cite
|
Sign up to set email alerts
|

New Aspects of Therapy of Hepatocellular Carcinoma Egyptian Patients

Abstract: Background: The purpose of this study was designed to investigate the potential impact of chemo and hormonal therapy drugs either with natural oils or other with vitamin E on HCC Egyptian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Mohamad et al [114] in their experimental study used 5-FU, oxaloplatin and tamoxifen as a treatment protocol for HCC patients with vitamin E and detected significant inhibition in GGT activity post treatment. In the same regard, Umarani et al [66] also found decline in enzyme activity after treatment with 5-FU compared to cancer induced rats.…”
Section: Discussionmentioning
confidence: 99%
“…Mohamad et al [114] in their experimental study used 5-FU, oxaloplatin and tamoxifen as a treatment protocol for HCC patients with vitamin E and detected significant inhibition in GGT activity post treatment. In the same regard, Umarani et al [66] also found decline in enzyme activity after treatment with 5-FU compared to cancer induced rats.…”
Section: Discussionmentioning
confidence: 99%